The regulatory and scientific context in the study of the medicinal use of cannabis in Peru - Wong-Salgado, Pedro; Moya-Salazar, Jeel; Contreras-Pulache, Hans; Pardo-Villarroel, Claudio (Frontiers in Medicine, 2025)
Cannabis has been historically utilized for medicinal purposes worldwide. However, it was classified as a controlled substance under the United Nations’ 1961 Single Convention on Narcotic Drugs, alongside coca and opium. This classification influenced many countries, including Peru, to adopt prohibitionist policies, even though the convention allowed medicinal use, scientific research, and even horticulture. Recent decades have witnessed a renewed interest in the therapeutic potential of cannabis, leading countries like Canada to establish medicinal frameworks. In 2017, Peru passed Law 30681, legalizing cannabis for medicinal use, scientific research, and pharmaceutical production through the obtention of licenses, and in 2021, Law 31312 allowed patient associations to grow and produce cannabis. Nevertheless, these regulations have proven insufficient, as no domestic production has taken place due to complex licensing requirements for both pharmaceutical companies and patient associations; the same scenario applies for scientific purposes. This article examines the regulatory challenges surrounding cannabis in Peru, focusing on scientific research. While the 2019 regulatory framework aimed to support medicinal access, it has fallen short in practice. Hard licensing process and stringent requirements have restricted scientific investigation, limiting it to observational studies and analysis of cannabis products available on the informal market. A recent study conducted between 2019 and 2023 analyzed native cannabis strains in four regions of Peru, highlighting the therapeutic potential of local cultivars. However, regulatory hurdles, such as sample obtention, transportation, and analysis, pose significant risks to researchers. The study suggests that Peru’s cannabis regulation requires urgent reforms, including simplifying licensing for scientific research, facilitating access for patients, and distinguishing personal cultivation from illicit drug trafficking. These changes are necessary to harness the medicinal potential of cannabis and support the development of local research and the possibility of local production.